Surgical treatment of the periocular keratoacanthoma - Zieliński, Tomasz (Klinika Oczna / Acta Ophthalmologica Polonica, 2011)
Keratoacanthoma (KA) is a benign epithelial neoplasm. It usually presents as a solitary rapidly growing lesion, which undergoes spontaneous resolution within a few months. The tumor is most commonly seen on sun exposed skin of the face, forearm and dorsal side of the hand. Periocular keratoacanthomas are relatively rare lesions and there are only a few data on clinical observation and treatment of KA in this area. Purpose: The goal of this paper is presentation of the own experiences in the treatment of the eyelids KA along with justification for the method chosen. Material and methods: Four patients with histopathological confirmed periocular KA were treated surgically. In two cases tumors were located on the lower lid, in one patient on upper lid, and in one case – in medial cantus. In all patients lesions were excised with the margin of intact tissue. In two cases defects were closed with sutures of the wound and in two others – with the use of forehead flap. Results: Postoperative period was without complications. In all cases histopathological examination confirmed diagnosis of KA and total excision. We obtained good aesthetic and functional results. There were no case of recurrence. Conclusions: Although the clinical presentation of KA is characteristic in most cases, it should always be differentiated from invasive SCC. A definitive diagnosis requires complete tumor excision. Early surgical treatment of periocular KA can prevent irreversible destruction of the eyelids.